Clinical course and pathogenicity of a Mycobacterium avium subsp. paratuberculosis isolate from scimitar oryx (Oryx dammah) in experimentally infected rabbits - Edith MALDONADO-CASTRO; Ana L. HERNÁNDEZ-REYES; Beatriz ARELLANO-REYNOSO; Carlos G. GUTIÉRREZ; Marta ALONSO-HEARN; Gilberto CHÁVEZ-GRIS (Spanish Journal of Agricultural Research, 2023)
Aim of study: To evaluate the infectivity of a MAP type C of a scimitar oryx (Oryx dammah) - included in an international conservation list - that showed clinical signs and granulomatous enteritis associated with paratuberculosis in rabbits (Oryctolagus cuniculus) using molecular, bacteriological and pathological methodologies.